Conjunctival habronemiasis in a square‐lipped rhinoceros (Ceratotherium simum). (28th March 2015) - Horowitz, Igal H.; Dubielzig, Richard R.; Botero‐Anug, Ana‐Maria; Lucio‐Forster, Araceli; Bowman, Dwight D.; Rosenzweig, Ariella B.; Frenkel, Shahar; Ofri, Ron
Abstract: A captive female square‐lipped rhinoceros born in 1993 had been showing intermittent signs of bilateral conjunctivitis and conjunctival proliferation since 1998. Periodic improvement was noted, especially in winter, but overall the condition had deteriorated over the years. Treatment with various topical, intralesional, and systemic antibiotics and glucocorticosteroids was largely ineffective, as were repeated dewormings. No primary cause for these lesions was found in biopsies taken in 2000 and 2006, although a severe infiltrate of numerous eosinophils was observed in the latter. As the condition worsened, secondary corneal changes were noted, and eventually vision was lost due to proliferative conjunctival tissue. Aggressive resection of the proliferating tissue in 2013 restored vision and submitted biopsies yielded a diagnosis of severe allergic conjunctivitis, eosinophilic granuloma, and habronematid ( Habronema or Draschia ) larval infection. As no other rhinoceros in the herd was affected, including two calves born to the patient who were in close contact with their mother, it was concluded the presentation was most likely due to a hypersensitivity reaction to the dead or dying larvae. Fly repellent is now regularly applied around the eye of this rhinoceros, and a protective face mask has been fitted. Ongoing periodic relapses are treated with oral ivermectin, topical antibiotics, and steroids.